2015
DOI: 10.4172/2157-7439.1000341
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Distribution of Non-targeted and Anti-CD44-conjugated Quantum Dots in Distinct Phenotypes of Breast Cancer

Abstract: Background: It has been postulated that most if not all cancers are hierarchically organized and contain distinct phenotypes of cells. In breast tumors CD44 + /CD24 -/EpCAM + phenotype had been shown to possess the properties of cancer stem-like cells, while CD44low/ -/CD24 + /EpCAM + cells represent more differentiated tumor cells that are often classified as luminal subtype of cancer. Quantum dots had already been used for imaging in vitro and in vivo, however the information about accumulation and time-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The cytotoxic effect of Au-MES NCs was more significant on MCF-7 cells than on MDA-MB-231 cells, along with higher intracellular ROS generation, which is in agreement with the results reported by other authors showing that MDA-MB-231 cells are more resistant to treatment and exhibit properties of cancer stem-like cells [ 70 , 71 ].…”
Section: Discussionsupporting
confidence: 91%
“…The cytotoxic effect of Au-MES NCs was more significant on MCF-7 cells than on MDA-MB-231 cells, along with higher intracellular ROS generation, which is in agreement with the results reported by other authors showing that MDA-MB-231 cells are more resistant to treatment and exhibit properties of cancer stem-like cells [ 70 , 71 ].…”
Section: Discussionsupporting
confidence: 91%
“…49,50 We previously showed that the antibody-QD complex not only recognizes its specific antigen, but also is engulfed inside the cells, while antibodies conjugated with commonly used organic fluorophore FITC remained on the cell membrane. 50 Although these results show promising potential of antibody-nanoparticle complexes to be used in both diagnostics and therapy, the success of such therapy is limited due to lack of tumor-specific antigens. 51 Ergo, nanoparticle transportation using cells that are naturally attracted to tumors emerged as a potential treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…There were successful attempts to use a similar quantum dot–chlorin e6 complex in photodynamic cancer therapy [15]. Another study has shown that QDs, conjugated with antibodies against CD44, a marker of cancer stem-like cells, can be selectively engulfed by breast cancer cells [16]. Such surface modifications increase the potential of QDs for the use in targeted cancer diagnostics and therapies.…”
Section: Introductionmentioning
confidence: 99%